Muscle selection and dosing in patients undergoing treatment with abobotulinumtoxinA for lower limb spasticity in real-world practice - Richard D. Zorowitz; Jorge Jacinto; Stephen Ashford; Mathieu Beneteau; Pascal Maisonobe; Christian Hannes; Alberto Esquenazi (Journal of Rehabilitation Medicine)
Objective: Describe abobotulinumtoxinA (aboBoNT-A) dosing parameters in the real-world management of lower limb spasticity (LLS).